Depression and Conversion to Dementia in Mild Cognitive Impairment - Fithry Rahma (HM Publisher, 2021)
Mild cognitive impairment (MCI) is a stage of aging that occurs between normal aging and dementia (precedes dementia). Patients with MCI have memory loss who is otherwise functioning normally and does not match the clinical diagnosis criteria for dementia. MCI is frequently accompanied by cognitive deficits and non-cognitive. One of the most frequent non-cognitive deficiencies is depression. Depression and mild cognitive impairment are closely associate particularly in the elderly and can progress into neurodegenerative disorders like dementia. This indicates that there is a connection that needs to be explored further. Through this review article, a theoretical review of the relationship between MCI with depression and its conversion to dementia.